The effects of mixing slurry water with type III gypsum on setting time, compressive strength and dimensional stability - Chindy Fransiska Br Nainggolan; Dwi Tjahyaning Putranti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Type III gypsum is a material used to make dental master casts. It may be added to an accelerator, such as slurry water, to shorten setting time. Calcium sulphate in slurry water may affect setting time, compressive strength and dimensional stability. Purpose: The study evaluated the effect of slurry water on the setting time, compressive strength and dimensional stability of type III gypsum. Methods: Eighty-one samples were made of type III gypsum, divided into three groups: group A was gypsum mixed with 1% slurry water, group B, gypsum mixed with 2% slurry water and group C, gypsum mixed with distilled water. Each sample was formed using a standardised master mould. For testing setting time, a cylindrical mould 25 mm in diameter and height was used; for compressive strength testing, the cylindrical mould was 20 mm in diameter and 40 mm in height; and for dimensional stability testing, a pair of cylindrical, ruled block and mould were used. Setting time was tested using Vicat’s apparatus; compressive strength was tested using a universal testing machine; and dimensional stability was tested using digital callipers. The data were analysed by one-way analysis of variance (ANOVA) and least significant difference (LSD) tests. Results: One-way ANOVA and LSD tests showed significant differences in the effect of slurry water on the setting time, compressive strength and dimensional stability of type III gypsum (p<0.05). Conclusion: The use of slurry water can shorten setting time, decrease compressive strength and increase dimensional change of type III gypsum.